The Role of Social Media Influencers in Shaping Customer Brand Engagement and Brand Perception - Lelasari Sijabat; Danny I. Rantung; Deske W. Mandagi (Jurnal Manajemen Bisnis, 2022)
In today's digital age, social media has emerged as a powerful tool that may reach a larger group. In order to reach current and potential customers, it is essential to employ the appropriate medium when marketing a product. The company's message will be effectively communicated to current and potential clients using social media influencers (SMI). The three primary questions underlying the issues raised are the focus of this investigation. (1) What is the effect of SMI on customer brand engagement (CBE) and customer brand perception (CBP)? (2) What is the effect of CBE on CBP? (3) Does CBE mediate the relationship between SMI and CBP? Setting the context of exploration of the Big Cola brand, a survey was conducted on the customer of Big Cola in West Java, Indonesia. The quantitative data were collected from 154 respondents from three regions: Bekasi, Bogor, and Depok, using purposive sampling technique, Structural equation modeling (SEM) utilizing SPSS and SmartPLS statistical software were then performed to analyze the data. The result revealed that SMI positively and significantly impacted CBE and CBP. Furthermore, CBE significantly and positively influences brand perception. Finally, CBE is found to be a significant mediator between SMI and brand CBP. Utilizing social media influencers in this promotion brand will enhance brand perception and consumer engagement, and as customer engagement rises, so will brand perception. These findings can help businesses make informed decisions on choosing the best promotional media.